Laboratory bioassay of fall armyworm (Spodoptera frugiperda) larva using various insecticides - Sharma, S.; Tiwari, S.; Thapa, R. B.; Pokhrel, S.; Neupane, S. (Journal of Agriculture and Forestry University, 2022)
Fall armyworm (FAW), Spodoptera frugiperda J.E. Smith, is a polyphagous invasive pest that seriously affects the maize crop. Various insecticides such as Spinosad, Chlorantraniliprole, Imidacloprid, Emamectin benzoate, Spinetoram and Neem-based insecticides are recommended to control this pest. However, their efficacy is not well studied in Nepal. Hence, a study was performed to evaluate the efficacy of the above-mentioned insecticides for FAW management in laboratory experiments. Seven different treatments (six insecticides such as Spinosad 45% SC, Chlorantraniliprole 18.5% SC, Imidacloprid 17.8% SL, Emamectin benzoate 5% SC, Spinetoram 11.7% SC, Neem-based pesticide (Azadirachtin 1500 ppm) and control (water spray) were evaluated in three replicated CRD design. Spinosad and Spinetoram were found effective for the FAW mortality in which > 50% mortality of the larva was obtained in twelve hours and > 90 % mortality in twenty-four hours. Likewise, Emamectin benzoate and Chlorantraniliprole also caused > 90% mortality within twenty-four hours. Azadirachtin and Imidacloprid were not as effective as other pesticides that caused only 17% larval mortality in the first twelve hours and 68% mortality in sixty hours. Similarly, Imidacloprid caused 8% larval mortality in twelve hours and 59% mortality in sixty hours. There was no mortality in water spray (control). This information gives an idea of all pesticides are not equally effective and efficient. Such information’s are important to the farmers to select the right insecticides for the control of FAW in maize crops.